Barriers affecting the English language speaking fluency of Bachelor of Arts in Communication students - Sorveto, Joyce P.; Ebenga, Timothy S.; Quinto, Joseph B. (ELT Forum: Journal of English Language Teaching, 2025)
For communication students, effective speaking is a vital skill since it directly shapes how they convey ideas and engage diverse audiences in global contexts. While English serves as the language of international communication, barriers in language learning can hinder their ability to communicate clearly, confidently, and professionally across cultures. To that effect, the preparation for aspiring professionals in the field of media, public relations, advertising, and other related areas should commence promptly. With these considerations, the researchers opted to conduct a study that aims to identify the barriers affecting the English-speaking fluency of Bachelor of Arts in Communication (BACOM) students in one prime university in Cordillera Administrative Region in the Philippines. A quantitative-descriptive study was used with two hundred and seventy (274) randomly selected participants. The study revealed that BACOM students experienced linguistic barriers, specifically the inability to produce specific words to express their thoughts, as well as psychological barriers, particularly those associated with a lack of self-confidence which affects their English-speaking fluency. Moreover, there is no significant difference in the level of agreement of BACOM students in the barriers affecting their English-speaking fluency according to sex or year level, implying that the students' sex and year level have no influence on their English language proficiency. Ultimately, this study provides recommendations for future research directions.